The Madrasah Memanggil Program as a Model for Combining Learning Activities in the Development of the Merdeka Belajar Kampus Merdeka (MBKM) Curriculum - Azizah, Kamilatin; Meydina, Shafira Rizkiy; Effendy, Moh. Hafid (UII Darullughah Waddawah Pasuruan, 2026)
Curriculum upgrading is essential in higher education to remain responsive to contemporary developments, including the implementation of the Merdeka Belajar Kampus Merdeka (MBKM) policy. One innovative curriculum development initiative is the Madrasah Memanggil program at the Master’s Program in Islamic Education (PAI), Universitas Islam Negeri Madura, which has the potential to serve as a new model for MBKM implementation. This study aims to describe the form, implementation, and contribution of the Madrasah Memanggil program to the development of the MBKM curriculum within the Master’s Program in PAI at UIN Madura. A descriptive qualitative method with a case study approach was employed. Data were collected from key informants, including the Head of the Master’s Program in PAI and the Chair of the East Java branch of the Indonesian National Madrasah Teachers Association (PGMNI), as well as relevant program documentation. Data analysis was conducted through data reduction, data display, and conclusion drawing. The findings indicate that the Madrasah Memanggil program functions as a collaborative and applicative platform that enables students to contribute directly to improving the quality of madrasah diniyah as educators, facilitators, and social volunteers. The program integrates several MBKM activities, such as thematic community service, teaching assistance, and educational internships, into a single cohesive scheme. Furthermore, it enriches students’ practical experience, strengthens socio-religious values, and enhances professional competencies, while fostering a transformative and contextually relevant MBKM-based curriculum development model.